Antenatally Diagnosed Posterior Urethral Valve: A Case Report - Islam, Mahzabeen; Rahman, Masudur; Dey, Sankar Narayan; Sharma, Netay Kumer; Farzana, Mir Naz (Community Based Medical Journal, 2016)
Posterior urethral valve (PUV) are the most common congenital obstructive lesion of the urethra and a common cause of obstructive uropathy in infancy. Clinical presentation depends on the severity of the obstruction. In case of severe obstruction, the diagnosis is usually made antenatally. Here, we present a case of antenatally diagnosed PUV of a fetus of a lady in her 9th month of pregnancy with mild lower abdominal pain for several hours. On ultrasound (US) examination, we found 36.5±2 weeks of pregnancy with mild to moderate oligohydramnios. Fetal urinary bladder was over distended; both the kidneys were grossly hydronephrotic and PUV like echo lucent area was seen at the prostatic region (Key hole sign). Emergency caesarian section (CS) was done and US of the baby showed typical US finding of PUV. The prognosis of antenatal diagnosis of PUV in early pregnancy is poor. But in this case due to the late onset of symptoms and as immediate necessary steps were taken, the baby was totally cured. This case was reported to aware about importance of antenatal anomaly scan and to share our experience. CBMJ 2016 January: Vol. 05 No. 01 P: 42-45